Just peacemaking : the new paradigm for the ethics of peace and war - Stassen, Glen Harold, 1936-2014. (Cleveland, The Pilgrim Press, 2008)
"Just Peacemaking is the product of 23 scholars across various denominations who have collaborated annually for six years to specify the 10 practical steps and develop the undergirding principles of this critical approach. Originally published in 1998 and revised in 2004, this new 2008 edition contains a new introduction and conclusion, as well as updated contents."--Jacket.
Support nonviolent direct action / John Cartwright, Susan Thistlethwaite -- Take independent initiatives to reduce threat / Glen Stassen -- Use cooperative conflict resolution / Steven Brion-Meisels [and others] --
Revised edition of: Just peacemaking : ten practices for abolishing war. c1998. 2004.
Includes bibliographical references (pages 215-234).
Keywords: Peace -- Religious aspects -- Christianity; Christianity and justice